Genome-Wide Identification and Comparative Analysis of the Teosinte Branched 1/Cycloidea/Proliferating Cell Factors 1/2 Transcription Factors Related to Anti-cancer Drug Camptothecin Biosynthesis in Ophiorrhiza pumila - Wang, Can; Hao, Xiaolong; Wang, Yao; Shi, Min; Zhou, Zhi-Gang; Kai, Guoyin (Frontiers in Plant Science, 2021)
Ophiorrhiza pumila (O. pumila; Op) is a medicinal herbaceous plant, which can accumulate camptothecin (CPT). CPT and its derivatives are widely used as chemotherapeutic drugs for treating malignant tumors. Its biosynthesis pathway has been attracted significant attention. Teosinte branched 1/cycloidea/proliferating cell factors 1/2 (TCP) transcription factors (TFs) regulate a variety of physiological processes, while TCP TFs are involved in the regulation of CPT biosynthesis remain unclear. In this study, a systematic analysis of the TCP TFs family in O. pumila was performed. A total of 16 O. pumila TCP (OpTCP) genes were identified and categorized into two subgroups based on their phylogenetic relationships with those in Arabidopsis thaliana. Tissue-specific expression patterns revealed that nine OpTCP genes showed the highest expression levels in leaves, while the other seven OpTCPs showed a higher expression level in the stems. Co-expression, phylogeny analysis, and dual-luciferase (Dual-LUC) assay revealed that OpTCP15 potentially plays important role in CPT and its precursor biosynthesis. In addition, the subcellular localization experiment of candidate OpTCP genes showed that they are all localized in the nucleus. Our study lays a foundation for further functional characterization of the candidate OpTCP genes involved in CPT biosynthesis regulation and provides new strategies for increasing CPT production.